The Moderating role of Islamic work ethics on the relationship between Organizational Citizenship behavior and Job Performance of Telecommunication companies in the Republic of Chad. - MAKI ISMAIL, MAHAMAT AHMAT; Asst. Prof. Dr. Maged Mustafa Mahyoub , (IJRDO - Journal of Business Management, 2019)
This study examines the Moderating role of Islamic work ethics on the relationship between Organizational Citizenship behavior and Job Performance among 152 employees in Telecommunication companies in the Republic of Chad.To achieves the research aims and objectives, a systematic research methodology has been followed. It has been determined that researcher has gather the primary as well as secondary sources of the study. Typically, the primary sources of gathering data helped in contributing towards the accumulation of fresh and unused research data. The surveys have been used for aggregating the primary data for this study. However, the methodology implied in this study is a quantitative method, and SPSS 23 package was used to investigate the relationship between Organizational Citizenship behavior and Job Performance with respect to the moderating role of Islamic Work ethics. Moreover, the result of this study shows significant relationship between Organizational Citizenship behavior, Job Performance and Islamic work ethics. This study found that Organizational Citizenship behavior has a significant contribution on Job Performance while Islamic Work ethics has a significant contribution and moderate the relationship between Organizational Citizenship behavior and Job Performance. Finally, based on research findings, the study’s results shown that there were significant relationships of all variables with the Islamic work ethics. All of the hypotheses were significant and accepted. Model   proved to be significant and good fit. Islamic work ethics proved to be a significant moderator between relationship of Organizational citizenship behavior and Job performance. It also proved to be a significant mediator between the relationship of Islamic work ethics and employee performance. This study has some limitations which have to be pointed out. Firstly, the current findings cannot be generalized across organizations due to the nature of the sample as the research was restricted to a few telecommunication companies only. Secondly, the limited size of each cultural group does not permit further investigation and analysis for each group independently. Third, the potential problem with respect to non-response is the possibility that non-respondents will differ from respondents with respect to the variables in question, in which case the survey estimates will be biased. Moreover, the study is silent about gender differences and does not report anything about the role of demographic variables in influencing outcome factors. In addition, the limitations of this research point towards topics to be addressed in the future. Therefore, future research should be conducted in more realistic settings in public sector organizations and include all level of employees as sample which supports the generalization of study’s results. The moderating role of Islamic work ethics may also influence on other important variables such as “employees work performance, employees’ motivation, and organizational justices and learning, job insecurity and satisfaction, and human talent development”Keywords: Organizational Citizenship behavior, Islamic work ethics and Job Performance